Factors of Formation of Economic Stability of Agricultural Enterprises - Dyachenko, V.S. (Економічний вісник Донбасу, 2013)
The practice of management based on market principles requires the formation of economic stability of the agricultural enterprises , taking into account all the factors, it will balance the economic system, will ensure efficient operation and forms the basis of the high potential of development in the future. У статті визначено, що практика господарювання на ринкових засадах вимагає від сільськогоспо- дарських підприємств формування економічної стійкості з урахуванням всіх чинників, що дозволить збалансувати економічну систему, забезпечить ефективне функціонування та утворить базис високого потенціалу їх розвитку в перспективі. В статье определено, что практика хозяйствования на рыночных принципах требует от сельскохозяйственных предприятий формирования экономической устойчивости с учетом всех факторов, это позволит сбалансировать экономическую систему, обеспечит эффективное функционирование и образует базис высокого потенциала их развития в перспективе.